Impacts of black soldier fly, Hermetia illucens, larval frass on lettuce and arugula production - Chavez, Maria Y.; Uchanski, Mark; Tomberlin, Jeffery K. (Frontiers in Sustainable Food Systems, 2024)
There are many benefits to producing insects for food and feed; they require fewer resources to produce, process, and distribute. The digested and undigested waste along with insect feces (i.e., frass) from the mass production of insects can be considerable. Black soldier fly larvae (BSFL) digestion of organic residue produces frass that is high in macronutrients that are desirable for plants, potentially serving as a partial replacement for fertilizer or growing media, such as peat. Arugula and lettuce were grown in greenhouse pot studies with treatments comprised of BSFL frass (BSF), vermicompost (VC), and peat, and compared to a 100% peat control (CP). Yield, productivity, greenness, and tissue nutrient concentrations were measured. Arugula and lettuce produced the highest fresh weight and dry weight in the BSFL treatments. Primary macronutrients (N, P, K) and Mg in both crops were also highest in the BSFL treatments. Secondary macronutrients (Ca, Mg, S) and micronutrients produced more variable results (B, Fe, Mn, Cu, Zn). Lettuce produced larger yields but had much lower concentrations of nutrients compared to arugula. In small amounts, 10-20%, BSFL frass can serve as a good replacement for peat in leafy green crops. It is an especially beneficial way to recycle organic side streams in different industries and reduce waste production overall.